New government: A new beginning ... A new opportunity? - Samhan Salgado, Fiorella (2021)
The question to be debated is that if after the candidate has promised its voters a set of management activities is to know about if you will be able to fulfill what he has promised his voters that in fact many of them seem not to care much the fulfillment of the electoral promises, since regularly vote and vote again to parties and individuals who have defrauded or cheated them again and again. However, this does not distract from recognizing the right to choose is the backbone of democracy, and that means not only the obligation to choose the best possible but the President elected to assume the political responsibility to fulfill the commitments expressed in promises programs, consistent with their own political ideology.